Ekspresi Seksualitas Perempuan dalam Novel Saman dan Larung Karya Ayu Utami - Riyanti, Evi; Tjahjono, Tengsoe; Suhartono, Suhartono (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The study of Ayu Utami's novel Saman and Larung in this study discusses the issue of female sexuality expression. The research method refers to qualitative with a semiotic study approach; Signifier and Signified Ferdinand De Saussure. The results of the study show that Ayu Utami's Saman and Larung novels have marker systems related to women's sexual expression in the category of erotic acts, namely sexual arousal by kissing, sexual expectations, sexual fantasies, masturbation, sexual stimulation and intercourse. The interwoven sign system represents markers related to sexual expression as resistance to the dominant (patriarchal) culture in order to achieve social equality, personality, identity, biological needs, sexual habits, relationships, thoughts and feelings.